2014
DOI: 10.2147/ijwh.s45397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structured counseling on women's selection of hormonal contraception in Israel: results of the CHOICE study

Abstract: BackgroundThe multinational CHOICE (Contraceptive Health Research Of Informed Choice Experience) study evaluated the effects of structured counseling on women’s contraceptive decisions, their reasons for making those decisions, and their perceptions of combined hormonal contraceptive (CHC) methods in eleven countries. The aim of this paper to present data from the 1,802 women participating in Israel’s CHOICE program.MethodsWomen (aged 17–40 years) who consulted their health care providers about contraception a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
2
2
0
1
Order By: Relevance
“…The number of the women who opted for hormonal methods was the highest in the selection of POPs followed by those who selected Injectable DMPA. This pattern for switching is consistent with previous findings of a comprehensive study conducted across five European countries, where changes in women's precounseling and post-counseling choices were statistically significant after counseling sessions [19][20][21]. However, this is the first-ever report of such choices being made by postpartum women pre-and post-counseling.…”
Section: My Friends Use It 61supporting
confidence: 90%
See 2 more Smart Citations
“…The number of the women who opted for hormonal methods was the highest in the selection of POPs followed by those who selected Injectable DMPA. This pattern for switching is consistent with previous findings of a comprehensive study conducted across five European countries, where changes in women's precounseling and post-counseling choices were statistically significant after counseling sessions [19][20][21]. However, this is the first-ever report of such choices being made by postpartum women pre-and post-counseling.…”
Section: My Friends Use It 61supporting
confidence: 90%
“…The effect of counseling on the selection of combined hormonal contraceptive methods in 11 countries was reported by others [19]. The poor usage of contraceptives as observed in the present study may be linked to the low education status of the postpartum women.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The fear of adverse effects was a significant reason for not practicing contraception. Other studies have shown the same concern in non‐Muslim populations (Bachar et al., 2002) and that counselling and education can help to improve contraception use and change prejudiced concepts (Yeshaya, Ber, Seidman, & Oddens, 2014).…”
Section: Discussionmentioning
confidence: 82%
“…Avusturya, Belçika, Çek Cumhuriyeti ve Slovakya, Hollanda, Polonya, İsveç, İsviçre, İsrail, Rusya ve Ukrayna'da doğum kontrol danışmanlığı öncesi ve sonrası kadınların kontraseptif seçeneklerini değerlendiren kesitsel bir çalışma olan CHOICE çalışmasında da benzer şekilde danışmanlığın kadınların tercihini etkilemede önemli bir etken olduğu sonucuna varılmıştır [17][18][19]. Bu bulguda bizim çalışmamızı desteklemektedir.…”
Section: Tablo 4 Katılımcıların Danışmanlık Sonrası Tercihlerinin En öNemli Sebepleri N: Hasta Sayısıunclassified